Pengaturan Hukum Tindak Pidana Penipuan Secara Online Dalam Perspektif Hukum Pidana di Indonesia - Rachman Ma'ruf; Indra Lamhot Sihombing; Fradhil Mensa; Raihana Raihana (Jurnal Hukum dan Sosial Politik, 2023)
The development of the era of technology and globalization is currently driving the development of information technology. The development of this information technology has spread throughout the world, not only in developed countries but has reached developing countries including Indonesia. This makes information technology has an important position for the progress of a country. The needs of people in the world are also growing so that information technology plays an important role today and in the future. Information technology brings great benefits and interests to countries in the world, especially Indonesia.